2010
DOI: 10.1002/app.33243
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐induced crystallization behavior of natural rubber and trans‐1,4‐polyisoprene crosslinked blends

Abstract: The strain-induced crystallization (SIC) behaviors of crosslinked blends based on natural rubber (NR) and trans-1,4-polyisoprene (TPI) with different content of TPI were probed explored by using synchrotron two-dimensional wide angle X-ray diffraction and dynamic mechanical analysis. The results showed that when TPI content is less than 70% no reflection peak of TPI but NR crystallite diffractions can be observed and the diffractions of TPI bform appear when TPI content is 70 wt % in the cocured blend. SIC of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The sudden increase in the master curve of G around 273 K disappeared by an adjustment of the cross-link density of NR to 2.76 × 10 −4 mol/cm 3 , allowing superimposition into the single master curve. [6] Thus, the melting point of the crystals in NR_2D was expected to be 333 K. On the other hand, the low stress at break, 1 MPa, of NR_6D at all temperatures may be attributed to inhibition of strain-induced crystallization by increasing cross-link density. This may be attributed to the inhibition of strain-induced crystallization by increasing cross-link density.…”
Section: Nr/sbr (3/7) Blendmentioning
confidence: 96%
See 2 more Smart Citations
“…The sudden increase in the master curve of G around 273 K disappeared by an adjustment of the cross-link density of NR to 2.76 × 10 −4 mol/cm 3 , allowing superimposition into the single master curve. [6] Thus, the melting point of the crystals in NR_2D was expected to be 333 K. On the other hand, the low stress at break, 1 MPa, of NR_6D at all temperatures may be attributed to inhibition of strain-induced crystallization by increasing cross-link density. This may be attributed to the inhibition of strain-induced crystallization by increasing cross-link density.…”
Section: Nr/sbr (3/7) Blendmentioning
confidence: 96%
“…[1][2][3][4][5][6] However, it is quite difficult to quantitatively investigate the relationship between the strain-induced crystallization and crack growth of an elastomer due to the difficulty of simultaneous observation of the strain-induced crystallization with breaking of the elastomer. [1][2][3][4][5][6] However, it is quite difficult to quantitatively investigate the relationship between the strain-induced crystallization and crack growth of an elastomer due to the difficulty of simultaneous observation of the strain-induced crystallization with breaking of the elastomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8(b)), which is in agreement with previous reports. 42,43,49 It can be observed that L 120 appears to slightly uctuate in composites without AE with increasing strain, which indicates that the increase in crystallinity is because of the increased number of crystallites. 41 However, L 120 is increased with the increase of AE at l ¼ 3 and it decreases signicantly on increasing the strain.…”
Section: Xrd Spectrummentioning
confidence: 97%
“…The crystallinity index CI and the average crystallite size L 120 (taking 120 plane as an example) were calculated according to the data in Fig. 7 using eqn (5) and (6); [42][43][44][45] then the results are found in Fig. 8.…”
Section: Xrd Spectrummentioning
confidence: 99%